Crime News Broadcasting in the Framework of Protection of the Rights of Suspects/Defendants - Ig Punia Atmaja Nr (Universitas Airlangga, 2022)
Crime news broadcasts on television are a part of press freedom to disseminate information to the public through printed or electronic media. Information delivery through electronic media such as television, particularly crime news, presents overviews of criminal events as if the audiences witness it straight from the crime scene. It shows the fact that. one on hand, crime news is broadcast widely on private television stations, while on the other hand there are rules for broadcasting crime news as regulated in Law Number 40 of 1999 on Press and Law Number 32 of 2002 on Broadcasting. Laws on press and broadcasting also regulate the establishment of Press Council that determines ‘journalist code of ethics’ and the Indonesian Broadcasting Commission (KPI) which sets the ‘broadcast program standards and broadcasting behavior guidelines’. These institutions supervise news or broadcasting as well as individuals or broadcasters that violate broadcasting rules or code of ethics. Crime news broadcasting that displays the face and identity of suspects or defendants is a violation to the principle of ‘Presumption of innocence’, that an individual should be assumed or considered innocent until the court proves that he/she is guilty. Crime news broadcasts impose effects on the suspects or defendants in receiving ‘due process of law’, and on the public prosecutor and judge investigating the case. Therefore, crime news broadcasting should be sought to not violate the code of ethics or rules as well as the rights of suspects or defendants.